12 MONTH’S ASSESSMENT OF CLINICAL EFFICACY OF RESIN MODIFIED GLASS IONOMER CEMENT AND FLOWABLE COMPOSITES IN RESTORATION OF NON-CARIOUS CERVICAL LESIONS, A RANDOMIZED CLINICAL TRIAL - Saghir, Atikah; Tehmina Rehman; Bushra Irum; Zarah Afreen; Ammarah; Faisal Nawaz Khan (Journal of Ayub Medical College Abbottabad, 2023)
Background: The objective of this study was to compare the clinical efficacy of Resin modified glass ionomer cement and Flowable composite in terms of retention, marginal adaptation and surface texture using United States Public Health Service criteria in non-carious cervical lesions measured over a period of one year. Methods: A Randomized Clinical Trial is conducted with Informed consent on 60 patients who are randomly allocated into 2 groups with at least 2 Non-Carious Cervical Lesions in each. Group 1 is used for Flowable Composite while group 2 is used for resin modified glass ionomer cement. A recall is maintained to draw conclusions between two materials in terms of occurrence of marginal adaptation, retention and surface texture, to show which material is superior to other. Results: Out of 30 restorations in 12 months follow up, only 19 found to be present in flowable composite group while in resin modified glass ionomer cement group, 28 are retained. Regarding margin integrity, Group 1 showed 21 intact margins whereas 23 margins were intact in group 2, while 18 and 25 showed smooth surface in flowable composite and Resin modified glass ionomer cement group respectively, on exploration. Conclusion: It can be concluded from our study that Resin modified glass ionomer cement is superior to Flowable composite in terms of retention (p=0.005) and surface texture (p=0.045) in restoration of non-carious cervical lesion.